Tailoring vertical phase distribution of quasi-two-dimensional perovskite films via surface modification of hole-transporting layer - Tiefeng Liu (Nature Portfolio, 2019)
Vertical phase distribution of quasi-two-dimensional perovskite plays vital roles in their optoelectronic properties. Here Liu et al. show that surface modification of the hole-transporting layer is an effective approach to control the vertical phase distribution and optimize the device efficiency.